Analisis Akuntabilitas Pengelolaan Alokasi Dana Desa Dalam Pelaksanaan Pembangunan Tahun Anggaran 2017-2021 (Studi Kasus Desa Adabang Kecamatan Titehena Kabupaten Flores Timur) - Beatriks Reo Weluk; Andreas Rengga; Konstantinus Pati Sanga (Student Scientific Creativity Journal, 2023)
This Study aimed to investigate the accountability of village fund allocation management in the implementation of defelopment in Adabang Village, Titehena Sub-district, East Flores Regency. This study was descrriptive qualitative that relied on primary and secondary data sources. Data was collected through observation, documentation, and interviews. Data was analyzed using some steps namely data collection, data reduction, data presentation, and conclusion drawing. The results indicated that the accountability of village fund allocation management had fulfilled several indicators of accountability for village fund allocation management, namely planning, implementing, and supervising stages. They were in accordance with the accountability indicators of village fund allocation management and applicable regulation. However, the accountability was not in accordance with the accountability indicator of village fund allocation management and applicable regulations since one type of accountability report was not submitted. Thus, the accountability stage was not in accordance With Permendagri Number 113 of 2014 and according to Sari and Wahidawati (2018).